Highly Emissive Covalent Organic Frameworks - Dalapati, Sasanka; Jin, Enquan; Addicoat, Matthew; Heine, Thomas; Jiang, Donglin (Journal of the American Chemical Society, 2016)
Highly luminescent covalent organic frameworks (COFs) are rarely achieved because of the aggregation-caused quenching (ACQ) of π–π stacked layers. Here, we report a general strategy to design highly emissive COFs by introducing an aggregation-induced emission (AIE) mechanism. The integration of AIE-active units into the polygon vertices yields crystalline porous COFs with periodic π-stacked columnar AIE arrays. These columnar AIE π-arrays dominate the luminescence of the COFs, achieve exceptional quantum yield via a synergistic structural locking effect of intralayer covalent bonding and interlayer noncovalent π–π interactions and serve as a highly sensitive sensor to report ammonia down to sub ppm level. Our strategy breaks through the ACQ-based mechanistic limitations of COFs and opens a way to explore highly emissive COF materials.